"Das neue Dorf. Eine Versammlung der 10. Brigade, die die Wanderfahne des Kollektivs erobert hat" - Neuman, ...,
"Das neue Dorf. Eine Versammlung der 10. Brigade, die die Wanderfahne des Kollektivs erobert hat".